2010
DOI: 10.1073/pnas.1014403107
|View full text |Cite
|
Sign up to set email alerts
|

pH-(low)-insertion-peptide (pHLIP) translocation of membrane impermeable phalloidin toxin inhibits cancer cell proliferation

Abstract: We find that pH-(low)-insertion-peptide (pHLIP)-facilitated translocation of phalloidin, a cell-impermeable polar toxin, inhibits the proliferation of cancer cells in a pH-dependent fashion. The monomeric pHLIP inserts its C terminus across a membrane under slightly acidic conditions (pH 6-6.5), forming a transmembrane helix. The delivery construct carries phalloidin linked to its inserting C terminus via a disulfide bond that is cleaved inside cells, releasing the toxin. To facilitate delivery of the polar ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
146
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 140 publications
(154 citation statements)
references
References 32 publications
7
146
0
1
Order By: Relevance
“…While studying membrane protein folding, we discovered a peptide called pH (low) insertion peptide (pHLIP) that reversibly folds and inserts across membranes in response to pH changes, and this discovery has led to a unique way to target acidic tissue. Our biophysical studies have revealed the molecular mechanism of pHLIP action (1-3), and we have shown that pHLIP can target acidic tissue and selectively translocate polar, cell-impermeable molecules across cell membranes in response to low extracellular pH (1,(4)(5)(6)(7)(8)(9). pHLIP conjugated with fluorescent dyes, PET [ 64 Cu-DOTA (1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid) and 18 F], single photon emission computed tomography (SPECT; 99 Tc) probes, and gold nanoparticles targets acidic tumors (1,4,5,10,11).…”
mentioning
confidence: 99%
“…While studying membrane protein folding, we discovered a peptide called pH (low) insertion peptide (pHLIP) that reversibly folds and inserts across membranes in response to pH changes, and this discovery has led to a unique way to target acidic tissue. Our biophysical studies have revealed the molecular mechanism of pHLIP action (1-3), and we have shown that pHLIP can target acidic tissue and selectively translocate polar, cell-impermeable molecules across cell membranes in response to low extracellular pH (1,(4)(5)(6)(7)(8)(9). pHLIP conjugated with fluorescent dyes, PET [ 64 Cu-DOTA (1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid) and 18 F], single photon emission computed tomography (SPECT; 99 Tc) probes, and gold nanoparticles targets acidic tumors (1,4,5,10,11).…”
mentioning
confidence: 99%
“…The pHLIP mechanism of action has been determined in liposomes (17) and has been used in cells for the delivery of fluorescent molecules (18). Furthermore, there is significant interest in this peptide as a probe or drug delivery system for cancerous cells and in inflammatory arthritis because of the low extracellular pH associated with these regions (18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…The pH-sensitive targeting agents we are developing are based on the action of a family of pHLIPs (pH Low-Insertion Peptides), which can "sense" acidity at the surface of cancer cells and deliver diagnostic and therapeutic molecules to tumors of different origins (20)(21)(22)(23)(24)(25). It was shown that pHLIP can promote fusion of liposomes with cancer cells and cellular delivery of various payloads (26,27), including small gold nanoparticles (26).…”
mentioning
confidence: 99%